The Moral Infra-structure of Market and Democracy. Reflections on the Adam Smith's Theory (2005)
The article presents an unconventional view of some concepts of Adam Smith's theoretical project, based on a contrast between the economic budgets exposed in The Wealth of Nations and the moral postulates that the author presented in Theory of Moral Senti